Assessing impact risk to tropical marine ecosystems from human activities with a Southeast Asian example - Culhane, Fiona; Austen, Melanie C.; Ashley, Matthew; Javier, Jonson; Kuit, Sui Hyang; Hung, Nguyen Phuc; Tran, Hau Duc; Praptiwi, Radisti A.; Sainal, Sainal; Justine, Eva; Wulandari, Prawesti; Broszeit, Stefanie; et al. (John Wiley and Sons Inc, 2024)
Society relies on intact marine ecosystems for ecosystem services such as nutrition, livelihoods, health and well-being. Yet, to obtain these benefits, we carry out activities, introducing pressures to ecosystems, damaging and degrading habitats and reducing their capacity to optimally provide ecosystem services. Biodiversity and ecosystem services are consequently being lost globally but impact chains from these activities are poorly understood, especially in tropical marine ecosystems. We identified for the first time impact chains linking activities with pressures they introduce in five tropical coastal and marine habitats, specifically through application in four Southeast Asian case study sites. Using expert elicitation based on existing evidence, we weighted each impact chain according to pressure extent, frequency and persistence, and habitat resistance and resilience. Assigning each impact chain an impact risk score allowed identification of activities and pressures introducing most risk, and habitats most under threat. Of 26 activities we considered, we found fishing activities, specifically trawling, gill nets and seine nets introduce most risk, along with tourism and recreation. Litter and pollution were among the greatest pressures on habitats, with coral reefs being most vulnerable overall. Destructive fishing practices were associated with physical pressures like abrasion, smothering and siltation and total habitat loss, while tourism activities were associated with organic enrichment, litter and pollution. The risk levels depended on the habitat and on local case study context. Synthesis and applications: A contextualised risk-based approach can help to prioritise sustainability issues for management in data-poor regions by making use of a range of knowledge types from local experts to broader scientific knowledge. A multisectoral, and ecosystem-based risk assessment can help decision makers to consider trade-offs in marine resource management and highlight priorities transparently, where coordination of multiple administrative organisations, sectors and local actors is required to meet multiple sustainability objectives. Physical pressures from fishing activities combined with pollution from tourism indicate effective management requires a multi-use zoning approach that not only considers impacts at the site of activities but also integrates regional coordination to tackle dispersive pressures from pollution or sediment disturbance that occur at a distance from the source.